Sevoflurane sedation attenuates early cerebral oedema formation through stabilisation of the adherens junction protein beta catenin in a model of subarachnoid haemorrhage: A randomised animal study. Issue 5 (May 2020) - Beck-Schimmer, Beatrice; Restin, Tanja; Muroi, Carl; Roth Z'Graggen, Birgit; Keller, Emanuela; Schläpfer, Martin
Abstract : BACKGROUND: Severe neurological impairment is a problem after subarachnoid haemorrhage (SAH). Although volatile anaesthetics, such as sevoflurane, have demonstrated protective properties in many organs, their use in cerebral injury is controversial. Cerebral vasodilation may lead to increased intracranial pressure (ICP), but at the same time volatile anaesthetics are known to stabilise the SAH-injured endothelial barrier. OBJECTIVE: To test the effect of sevoflurane on ICP and blood–brain barrier function. DESIGN: Randomised study. PARTICIPANTS: One hundred male Wistar rats included, 96 analysed. INTERVENTIONS: SAH was induced by the endoluminal filament method under ketamine/xylazine anaesthesia. Fifteen minutes after sham surgery or induction of SAH, adult male Wistar rats were randomised to 4 h sedation with either propofol or sevoflurane. MAIN OUTCOME MEASURES: Mean arterial pressure (MAP), ICP, extravasation of water (small), Evan's blue (intermediate) and IgG (large molecule) were measured. Zonula occludens-1 (ZO-1) and beta-catenin (β-catenin), as important representatives of tight and adherens junction proteins, were determined by western blot. RESULTS: Propofol and sevoflurane sedation did not affect MAP or ICP in SAH animals. Extravasation of small molecules was higher in SAH-propofol compared with SAH-sevoflurane animals (79.1 ± 0.9 vs. 78.0 ± 0.7%, P  = 0.04). For intermediate and large molecules, no difference was detected ( P  = 0.6 and P  = 0.2). Both membrane and cytosolic fractions of ZO-1 as well as membrane β-catenin remained unaffected by the injury and type of sedation. Decreased cytosolic fraction of β-catenin in propofol-SAH animals (59 ± 15%) was found to reach values of sham animals (100%) in the presence of sevoflurane in SAH animals (89 ± 21%; P  = 0.04). CONCLUSION: This experiment demonstrates that low-dose short-term sevoflurane sedation after SAH in vivo did not affect ICP and MAP and at the same time may attenuate early brain oedema formation, potentially by preserving adherens junctions. TRIAL REGISTRATION: No 115/2014 Veterinäramt Zürich. Abstract : Supplemental Digital Content is available in the text